Mechanistic studies to understand metastasis breast cancer: towards the effects of microbial derivatives of testosterone propionate on MDA-MB 231 cell migration / Assoc. Prof. Sadia Sultan … [et al.] - Sultan, Sadia; Ali Shah, Syed Adnan; Ashraf, Kamran; Mohd Fauzi, Fazlin; Hasan, Mizaton Hazizul; Salim, Fatimah (Faculty of Pharmacy, 2023)
Cancer is a worldwide disease that can affect everyone. It is a genetic disease that arises by changing the function of genes such as proto-oncogenes, tumour suppressor gene and DNA repair gene. Cancer begins when cells grow uncontrollably and form a mass called tumour. Cancer can be classified into two, which are benign tumours or malignant tumours. A benign tumour is localised in the cells while a malignant tumour is a tumour that tends to invade and spread in the body. One of the most common cancers that affect women worldwide is breast cancer. It is a heterogeneous disease that affects one in every eight women worldwide. Breast cancer is cancer that develops in breast cells. Cancer is derived from lobules and ducts of the mammary gland. In breast cancer, abnormal growth of cells will occur from epithelial cells that line both lobules and ducts. Breast cancer can be categorised into two types, which are invasive and non-invasive. Invasive breast cancer is cancer that spreads into surrounding tissues while non-invasive breast cancer does not spread from the original tissues. According to American Cancer Society (ACS), in 2018, there are 266,120 new cases of invasive cancer and 63,960 new cases of carcinoma in situ are estimated to be diagnosed. This led to breast cancer ranked as the second cause of cancer-related death in females.